MENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN MEDIA GAMBAR PADA MATA PELAJARAN BAHASA INDONESIA PESERTA DIDIK SEKOLAH DASAR - Asep Priatna; Siti Nurhalimah (STKIP Subang, 2019)
This research is motivated by the low skill of writing essays for grade 3 students in elementary school. Based on the observation results, the low ability of students in writing poetry on Indonesian language subjects is due to the lack of effective learning created by the teacher, ineffectiveness due to the inaccurate strategies applied by the teacher in learning. The research method used is Classroom Action Research (CAR). The reason for using this method is to find out how the use of picture media in improving poetry writing skills in this classroom action research was conducted on Indonesian language learning in SDN Layapan, Purwadadi District, Subang, 2017/2018 academic year in the first semester. Based on the results of the study concluded as follows: 1) Poetry writing skills using media images can be improved by means of; students observe images, explore their initial knowledge of images, write words that are appropriate to the image and develop ideas and ideas into whole poems by paying attention to the elements of poetry. The increase in poetry writing skills can be seen from the average value of students increasing from the initial conditions which only have an average value of 55 and in the first cycle of 63, cycle 2 the average value obtained by students is 72. And then in the cycle III the average value obtained by students is 86 which is included in criterion A (very good); 2) Activity of students at the time of research using picture media for third grade students of SDN Layapan, showing an increase in writing skills for students. After doing the research as a whole the average value of students increases in cycle 1 the average value of students is 67, then in the second cycle then in the second cycle the average value of students is 79, and in the third cycle that is equal to 92 who can categorized as criterion A (very good).